1995
DOI: 10.1103/physrevd.51.6917
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical quantization of circular strings in de Sitter and anti–de Sitter spacetimes

Abstract: We compute the exact equation of state of circular strings in the (2+1) dimensional de Sitter (dS) and anti de Sitter (AdS) spacetimes, and analyze its properties for the different (oscillating, contracting and expanding) strings. The string equation of state has the perfect fluid form P = (γ − 1)E, with the pressure and energy expressed closely and completely in terms of elliptic functions, the instantaneous coefficient γ depending on the elliptic modulus. We semi-classically quantize the oscillating circular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(168 citation statements)
references
References 17 publications
10
158
0
Order By: Relevance
“…Here we wish to study pulsating string solution in the sub sectors of the deformed background as they are more stable than rotating ones [37]. After the inception of the pulsating string in [38], they have been studied both in AdS and non-AdS background [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Jhep03(2015)010mentioning
confidence: 99%
“…Here we wish to study pulsating string solution in the sub sectors of the deformed background as they are more stable than rotating ones [37]. After the inception of the pulsating string in [38], they have been studied both in AdS and non-AdS background [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Jhep03(2015)010mentioning
confidence: 99%
“…However one important class of strings, pulsating strings, have not received much attention so far. They have been studied in AdS 5 × S 5 [18,19,20,21,22,23,24,25], AdS 4 × CP 3 [26,27] and other backgrounds [28], [29], [30], [31]. In the context of deformed geometry it was found that pulsating and rotating strings in AdS 5 × S 5 are images of point like strings living in the deformed space [32].…”
Section: Introductionmentioning
confidence: 99%
“…One particular example where one can go much beyond the semiclassical approximation is that of highly boosted point-like strings, corresponding to states of large R-charge [7]. Other examples include truly extended classical string states, such as folded strings in the leading Regge trajectory, stabilized by a large spin S, and/or large R-charge quantum number J (see also [8]- [13] and [14] for an earlier work.). In particular, for very large rotating strings in AdS 5 in global coordinates, there is a dispersion relation…”
Section: Introductionmentioning
confidence: 99%